Model uncertainty and the equilibrium value of the real effective euro exchange rate - Carsten Detken; Alistair Dieppe; Jérôme Henry; Carmen Marin; Frank Smets (European Central Bank (ECB), 2002)
On the basis of historical data aggregated over the period 1973 to 2000, we estimated four different equilibrium exchange rate models for the synthetic euro. Using the same data set, variable definitions and sample period offers the possibility to assess the uncertainty surrounding such equilibrium levels, both from a statistical and a theoretical perspective. We employed reduced form co-integration models, a structurla VAR, a Natrex model (estimated in structural form) and the ECB's small-sized euro area wide macro-economic model. In this order the approaches feature an increasing degree of 'structure', in the sense of the constraints based on economic theory embedded in the econometric models that were estimated. The results confirm the high leikelihood for the euro ahving been undervalued in Q4 2000, while stressing the significant empirical and theoretical uncertainty with respect to the equilibrium exchange rate level.
Keywords: F31; F32; 330